(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To develop and assess the validity and reliability of a survey questionnaire regarding violence against nurses participating in pre-hospital emergency care in Vietnam. Method: The instrument was developed in three phases: item generation, expert-based content validation, and pilot testing for reliability. Results: The newly developed questionnaire demonstrated excellent content validity, with all items achieving a CVI, I-CVI of 1 and an S-CVI/Ave of 1. The KR-20 reliability coefficient was 0.91. Test-retest reliability conducted after a two-week interval yielded a KR-20 of 0.90. Spearman’s correlation was employed to assess the stability and internal consistency of the questionnaire, resulting in a coefficient of 0.99 (p < 0.01). When administered to a sample of 600 emergency prehospital care nurses, the questionnaire achieved a KR-20 of 0.91 following the test-retest reliability assessment after two weeks. Conclusion: The questionnaire is valid and reliable for assessing workplace violence among pre-hospital emergency nurses in Vietnam and serves as a practical tool for its identification and prevention.